Catalyst with precious metals supported on grain boundaries and surfaces, its manufacturing method and uses
Patent Information
- Application Number
- JP2024542106
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-14
- Filing Date
- 2023-02-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-02-13
AI Technical Summary
【0026】 要約すると、本発明は粒界及び表面に貴金属を担持した触媒、製造方法及び用途を提供し、前記触媒において貴金属Gはアルミナ及び/又は希土類マンガンジルコニウム複合酸化物の粒界及び表面に分散され、多相界面を形成し、以下の有益な技術的効果を取得し、1、当該多相界面はより大きな立体障害及びより強いアンカー作用を有し、貴金属の高温移動、凝集及び成長を抑制し、貴金属の高温安定性及び触媒性能を向上させ、貴金属の使用量を低減させることができ、2、当該多相界面は相乗触媒効果を有し、格子酸素活性化エネルギーを低下させて活性酸素量を増加させ、NO酸化率及び低温触媒活性を向上させることができる。また、本発明は理論的に算出された元素表面エネルギーと酸素空孔形成エネルギーの差に基づいて、シェル又は/及びコア元素の種類と含有量を設計することにより、希土類マンガンジルコニウム複合酸化物の熱安定性及び酸素貯蔵放出性能を総合的に向上させ、且つ、本発明は理論的に算出された元素表面エネルギーと酸素空孔形成エネルギーの差に基づいて、勾配構造における元素種類と含有量を設計し、結晶粒の径方向の内側から外側に向かって特定元素の含有量を徐々に増加させ又は徐々に減少させ、希土類マンガンジルコニウム複合酸化物の熱安定性及び酸素貯蔵放出性能を総合的に向上させる。
Smart Images

Figure 2025505107000001_ABST
Abstract
Description
[Technical field]
[0001] <CROSS REFERENCE TO RELATED APPLICATIONS> This application is filed based on a Chinese patent application having application number 202210135505.3 and filing date of February 14, 2022, and claims priority to the Chinese patent application, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to the technical field of catalysts carrying precious metals, and in particular to catalysts carrying precious metals on grain boundaries and surfaces, honeycomb-type precious metal catalysts, and their manufacturing methods and uses. [Background technology]
[0003] In recent years, lean-burn engines (diesel engines and lean-burn gasoline engines) have been attracting attention due to their good fuel economy and low greenhouse gas emissions. However, the exhaust gas from lean-burn engines is NO x Diesel exhaust gases are emitted from diesel engines, which cause serious damage to human health. Currently, governments around the world are placing increasingly stricter requirements on environmental protection for diesel exhaust gases. From the reaction mechanism, HC and CO are easily oxidized and removed in the presence of oxygen, while NOx is easily removed. x The reaction is relatively complicated, and it is necessary to manufacture a highly efficient catalyst with high oxygen storage capacity and low-temperature high activity, so as to achieve a relatively high removal effect. During high-speed driving, the temperature of diesel exhaust gas can reach 600°C or more, so the catalyst is required to still have high activity under high-temperature conditions. The catalytic precious metals in the prior art are prone to agglomeration at high temperatures and have poor dispersibility, which means they cannot effectively treat diesel exhaust gas, causing environmental pollution, and therefore it is necessary to manufacture a highly stable and highly active diesel NOx catalyst. x There is no time to waste in developing a highly efficient catalyst for purifying exhaust gas.
[0004] Diesel oxidation catalysts (DOCs) have been attracting attention in recent years. DOCs have a strong NO oxidation ability, and SCR low-temperature NO xThe conversion rate can be significantly improved (Russell A, Epling W S. Catalysis Reviews, 2011, 53 (4): 337 ~ 423). Currently, commercial DOC catalysts have many drawbacks, such as the tendency of precious metals to aggregate and become inactive at high temperatures, and high reaction temperatures (Caliskan H, Mori K. Energy, 2017, 128: 128 ~ 144). Therefore, research into high precious metal dispersion and high activity DOC catalysts is the focus of diesel aftertreatment systems. In order to obtain higher NO catalytic oxidation performance, it is necessary to develop high stability and high activity DOC catalysts. Summary of the Invention [Problem to be solved by the invention]
[0005] Based on the above-mentioned situation of the prior art, the object of the present invention is to provide a catalyst with a precious metal supported on the grain boundary and surface, a preparation method and use thereof, in which the precious metal is uniformly dispersed on the grain boundary and surface of alumina and / or rare earth manganese zirconium composite oxide, forming a multi-phase interface, inhibiting the high-temperature migration, aggregation and growth of the precious metal, improving the high-temperature stability and catalytic performance of the precious metal, reducing the amount of precious metal used, and reducing the lattice oxygen activation energy to increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity. [Means for solving the problem]
[0006] In order to achieve the above object, according to a first aspect of the present invention, there is provided a catalyst having a precious metal supported on grain boundaries and surfaces, the catalyst comprising a precious metal G, alumina and / or a rare earth manganese zirconium composite oxide, the precious metal G being dispersed on grain boundaries and surfaces of the alumina and / or rare earth manganese zirconium composite oxide, and the rare earth manganese zirconium composite oxide having a general chemical formula of RE a Mn b Zr c M d O (2-δ) D β where: RE is a rare earth element, M is a cation doping element, and D is an anion doping element; 0.1≦a≦0.5, 0.05≦b≦0.3, 0.2≦c≦0.8, 0≦d≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d=1.
[0007] According to a second aspect of the present invention, there is provided a honeycomb-type precious metal catalyst, the catalyst comprising a honeycomb carrier, a precious metal G and an active coating, the active coating being alumina and / or rare earth manganese zirconium composite oxide RE. a Mn b Zr c M d O (2-δ) D β said precious metal G being dispersed at the grain boundaries and surface of the active coating, wherein RE is a rare earth element, M is a cation doping element, and D is an anion doping element; 0.1≦a≦0.5, 0.05≦b≦0.3, 0.2≦c≦0.8, 0≦d≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d=1.
[0008] Furthermore, the proportion of the rare earth manganese zirconium composite oxide in the total mass of the active coating is 0 to 100%, and preferably 30 to 70%.
[0009] Furthermore, the noble metal G at the grain boundaries and on the surface is in a metallic state, or in a metallic and oxidized state.
[0010] Furthermore, the precious metal G includes one or a combination of one or more of Pt, Pd, Rh, Ir, Os, Ru, Au, and Ag, preferably one or a combination of one or more of Pt, Pd, Rh, and Ru, and more preferably a combination of Pt and Pd.
[0011] Furthermore, the rare earth element RE comprises one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc, and is preferably one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Yb, Y; the doping element M comprises one or a combination of one or more of transition metal elements, alkaline earth metal elements, Al, Si, Sn; and the doping element D comprises one or a combination of one or more of anions N, P, F.
[0012] Furthermore, the transition metal element is one or a combination of one or more of Fe, Co, Ni, Cu, Zn, Ti, Hf, V, Cr, Nb, Mo, and W, and is preferably one or a combination of one or more of Fe, Co, Ni, Cu, and Hf, and the alkaline earth metal element is one or a combination of one or more of Mg, Ca, Sr, and Ba, and is preferably one or a combination of one or more of Sr and Ba.
[0013] Furthermore, the amount of the precious metal G supported in the catalyst is, in mass percentage, 0.01% to 2%, and preferably 0.1% to 1%.
[0014] Furthermore, the amount of the precious metal G supported in the catalyst is 0.03 to 2.0 g / L, and preferably 0.15 to 1.5 g / L.
[0015] Furthermore, the rare earth manganese zirconium composite oxide in the catalyst has a core-shell structure, the core containing rare earth and zirconium elements, and the shell containing rare earth and manganese elements.
[0016] Furthermore, the rare earth manganese zirconium composite oxide in the catalyst contains a rare earth zirconium oxide having an element gradient distribution structure.
[0017] Furthermore, the material of the honeycomb carrier is a porous ceramic or a metal, and further, the honeycomb carrier may be one or a combination of one or more of cordierite, cordierite-alumina, silicon nitride, silicon carbide, alumina-silica-magnesia, zirconium silicate-silica sinter, magnesium silicate, and aluminum silicate.
[0018] According to a third aspect of the present invention, there is provided a method for producing a catalyst having a noble metal supported on the grain boundaries and surface according to the first aspect of the present invention, A step S1 of uniformly mixing a rare earth manganese zirconium composite oxide and / or alumina with a liquid salt of a precious metal G and drying the mixture; Step S2, which performs one or two heat treatments on the product obtained in step S1; and Step S3, in which the product obtained in Step S2 is roasted once or twice in air or a reducing atmosphere to obtain a catalyst in which a precious metal is supported on the grain boundaries and surfaces of a rare earth manganese zirconium composite oxide and / or alumina.
[0019] According to a fourth aspect of the present invention, there is provided a method for producing the honeycomb-type precious metal catalyst according to the second aspect of the present invention, the honeycomb-type precious metal catalyst is coated with one or more coating materials in a hierarchical or compartmental manner, the coating materials being alumina, rare earth manganese zirconium composite oxide, alumina with precious metal supported on grain boundaries and surfaces, rare earth manganese zirconium composite oxide with precious metal supported on grain boundaries and surfaces, or a mixture of rare earth manganese zirconium composite oxide and alumina with precious metal supported on grain boundaries and surfaces, the production steps being: Step A1: uniformly mixing the one or more coating materials with an adhesive, an acidity regulator and water in one or multiple steps to prepare a coating slurry; Step A2 of applying the coating slurry obtained in step A1 to a honeycomb carrier in one step or multiple steps, or applying the coating slurry to the honeycomb carrier in a sectioned or layered manner, and drying the coating slurry; and step A3 of heat-treating and / or roasting the product obtained in step A2 in air or a reducing atmosphere to obtain a catalyst having a precious metal supported on the honeycomb-type grain boundaries and surfaces.
[0020] According to a fifth aspect of the present invention, there is provided a method for producing a honeycomb-type precious metal catalyst according to the second aspect of the present invention, comprising uniformly mixing rare earth manganese zirconium composite oxide and / or alumina, liquid salt of precious metal G, acidity regulator, adhesive and water in one or multiple steps to prepare a coating slurry, coating the slurry on a honeycomb carrier in one or multiple steps, or coating the honeycomb carrier in sections or layers, and drying the honeycomb carrier, and then heat-treating or / and roasting the dried honeycomb carrier in a reducing atmosphere to obtain a catalyst carrying precious metal on the honeycomb-type grain boundaries and surfaces.
[0021] Furthermore, the heat treatment temperature is 200 to 750° C. and the heat treatment time is 0.5 to 24 hours, and preferably, the heat treatment temperature is 400 to 700° C. and the heat treatment time is 1 to 12 hours.
[0022] Further, the roasting temperature is 400 to 850° C. and the roasting time is 0.5 to 24 hours, and preferably, the roasting temperature is 450 to 750° C. and the roasting time is 1 to 12 hours.
[0023] Further, the liquid salt of the precious metal G may include one or a combination of one or more of the following molten salts or aqueous solutions: chloride salts, nitrates, acetates, and citrates.
[0024] Additionally, the reducing atmosphere includes one or more of CO and H2.
[0025] According to a sixth aspect of the present invention, there is provided uses of the catalysts provided according to the first and second aspects of the present invention in the fields of automobile exhaust gas purification, industrial organic exhaust gas treatment, natural gas catalytic combustion, petrochemistry, hydrogen energy, and batteries. Effect of the Invention
[0026] In summary, the present invention provides a catalyst with a precious metal supported on the grain boundary and surface, a preparation method and use thereof, in which the precious metal G is dispersed on the grain boundary and surface of alumina and / or rare earth manganese zirconium composite oxide to form a multi-phase interface, which provides the following beneficial technical effects: 1. the multi-phase interface has greater steric hindrance and stronger anchoring effect, which inhibits the high-temperature migration, aggregation and growth of the precious metal, improves the high-temperature stability and catalytic performance of the precious metal, and reduces the amount of precious metal used; 2. the multi-phase interface has a synergistic catalytic effect, which reduces the lattice oxygen activation energy and increases the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity. In addition, the present invention designs the type and content of shell and / or core elements based on the theoretically calculated difference between element surface energy and oxygen vacancy formation energy, thereby comprehensively improving the thermal stability and oxygen storage / release performance of the rare earth manganese zirconium composite oxide. Also, the present invention designs the type and content of elements in a gradient structure based on the theoretically calculated difference between element surface energy and oxygen vacancy formation energy, and gradually increases or decreases the content of a specific element from the radial inner side to the radial outer side of the crystal grain, thereby comprehensively improving the thermal stability and oxygen storage / release performance of the rare earth manganese zirconium composite oxide. [Brief description of the drawings]
[0027] [Figure 1] 1 is a flowchart of a method for producing a catalyst having a precious metal supported on the grain boundaries and the surface according to an embodiment of the present invention. [Diagram 2] 2 is a flowchart showing a method for manufacturing a honeycomb-type precious metal catalyst according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below with reference to the drawings in conjunction with specific embodiments. It should be understood that these descriptions are illustrative and do not limit the scope of the present invention. In addition, in the following description, descriptions of known structures and techniques are omitted to avoid unnecessary confusion of the concept of the present invention.
[0029] The embodiment of the present invention provides a catalyst with precious metal supported on the grain boundary and surface, the catalyst comprises precious metal G, alumina and / or rare earth manganese zirconium composite oxide, the precious metal G is dispersed on the grain boundary and surface of the alumina and / or rare earth manganese zirconium composite oxide, the precious metal G is simultaneously present on the grain boundary and surface of the alumina and / or rare earth manganese zirconium composite oxide, the new grain boundary precious metal supporting site can be fully utilized, and the distribution density of the precious metal supported on the surface can be reduced, a grain boundary-surface double anchor structure can be formed, the high temperature migration and aggregation of the precious metal can be inhibited, and the thermal stability of the precious metal can be improved. The chemical formula of the rare earth manganese zirconium composite oxide is RE a Mn b Zr c M d O (2-δ) D β where: RE is a rare earth element, M is a cation doping element, and D is an anion doping element; 0.1≦a≦0.5, 0.05≦b≦0.3, 0.2≦c≦0.8, 0≦d≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d=1.
[0030] An embodiment of the present invention further provides a honeycomb-type precious metal catalyst, the catalyst comprising a honeycomb carrier, a precious metal G and an active coating, the active coating being alumina and / or rare earth manganese zirconium composite oxide RE. a Mn b Zr c M d O (2-δ) D βThe precious metal G is dispersed on the grain boundaries and surface of the active coating, and the precious metal G is simultaneously present on the grain boundaries and surface of the active coating, which can not only fully utilize the new precious metal loading sites on the grain boundaries, but also reduce the distribution density of the precious metal loaded on the surface, form a grain boundary-surface double anchor structure, inhibit the high-temperature migration and aggregation of the precious metal, and improve the thermal stability of the precious metal, wherein: RE is a rare earth element, M is a cation doping element, and D is an anion doping element; 0.1≦a≦0.5, 0.05≦b≦0.3, 0.2≦c≦0.8, 0≦d≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d=1.
[0031] The precious metal G may be, for example, one or a combination of more than one of Pt, Pd, Rh, Ir, Os, Ru, Au and Ag, preferably one or a combination of more than one of Pt, Pd, Rh and Ru, more preferably a combination of Pt and Pd, the molar ratio of the precious metal G in the grain boundary is 10-70mol%, the precious metal G in the grain boundary or on the surface is in a metallic state, or in a metallic state and an oxidized state, preferably, it is advantageous to convert to a metallic state due to the catalytic effect. In the catalyst in which the precious metal is supported on the grain boundary and on the surface, the amount of the precious metal G supported is 0.01%-2% by mass percentage, preferably 0.1%-1%, more preferably 0.1%-0.5%. In the honeycomb-type precious metal catalyst, the amount of the precious metal G supported is 0.03-2.0g / L, preferably 0.15-1.5g / L. The proportion of the total mass of the rare earth manganese zirconium composite oxide in the active coating is 0 to 100%, and preferably 30 to 70%.
[0032] The catalyst with precious metal supported on grain boundaries and surfaces and the honeycomb-type precious metal catalyst provided by the embodiments of the present invention contain precious metal G on the grain boundaries and surfaces of the rare earth manganese zirconium composite oxide and / or alumina in the catalyst, forming a multi-phase interface, which has greater steric hindrance and stronger anchoring effect, inhibits the high-temperature migration, aggregation and growth of the precious metal, improves the high-temperature stability of the precious metal, and can reduce the amount of precious metal used. In addition, the multi-phase interface has a synergistic catalytic effect, which reduces the lattice oxygen activation energy and increases the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.
[0033] The rare earth manganese zirconium composite oxide in the catalyst provided by the embodiment of the present invention has a core-shell structure, the core includes rare earth and zirconium elements, and the shell includes rare earth and manganese elements. For other features and advantages of the core-shell structure of the rare earth manganese zirconium composite oxide, please refer to the Chinese patent application with application number ZL201910833257.8 filed on September 4, 2019 and the invention title "Core-shell structure rare earth manganese / cerium zirconium composite compound and preparation method and catalyst" and its entire content description. The present invention designs the type and content of shell and / or core elements based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, and comprehensively improves the thermal stability and oxygen storage and release performance of the rare earth manganese zirconium composite oxide.
[0034] The rare earth manganese zirconium composite oxide in the catalyst provided by the embodiment of the present invention includes a rare earth zirconium-based oxide with an element gradient distribution structure. For other features and advantages of the element gradient distribution structure of the rare earth zirconium-based oxide, please refer to the Chinese patent application with application number CN202010982979.2, filed on September 17, 2020, and the invention title "Cerium zirconium composite oxide with element gradient distribution and its manufacturing method" and its entire content description. Based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, the present invention designs and controls the element types and contents in the gradient structure, and gradually increases or decreases the content of a specific element from the inside to the outside in the radial direction of the crystal grain, thereby comprehensively improving the thermal stability and oxygen storage and release performance of the rare earth manganese zirconium composite oxide.
[0035] In the rare earth manganese zirconium composite oxide, the rare earth element RE includes one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc, and is preferably one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Yb, and Y. The doping element M is one or a combination of one or more of a transition metal element, an alkaline earth metal element, and Al, Si, and Sn, and the doping element D includes one or a combination of one or more of anions N, P, and F.
[0036] In the rare earth manganese zirconium composite oxide, the transition metal element is one or a combination of one or more of Fe, Co, Ni, Cu, Zn, Ti, Hf, V, Cr, Nb, Mo, and W, and is preferably one or a combination of one or more of Fe, Co, Ni, Cu, and Hf, and the alkaline earth metal element is one or a combination of one or more of Mg, Ca, Sr, and Ba, and is preferably one or a combination of one or more of Sr and Ba.
[0037] An embodiment of the present invention further provides a method for producing a catalyst having a precious metal supported on the grain boundaries and surface, similar to the method provided by the above embodiment, the flow chart of which is shown in FIG. 1 and includes the following steps S1 to S3:
[0038] In step S1, the rare earth manganese zirconium composite oxide and / or alumina are uniformly mixed with the liquid salt of the precious metal G, and then dried, the liquid salt of the precious metal G being one or a combination of one or more of the molten salt or aqueous solution of the chloride salt, the nitrate salt, the acetate salt, and the citrate salt. The drying temperature is 50 to 200°C, and the drying time is 1 to 48 hours.
[0039] In S2, the composite compound hydride obtained in step S1 is heat-treated once or twice, the heat-treatment temperature is 200-750°C, and the heat-treatment time is 0.5-24h, preferably the heat-treatment temperature is 400-700°C, and the heat-treatment time is 1-12h. In order to meet the special requirements of different applications for the performance of the catalyst with precious metals supported on the grain boundary and surface, it is necessary to adjust or change the microstructure of the catalyst, and therefore it is necessary to adopt different heat-treatment regimes, for example, to carry out heat treatment in stages to make more precious metals more uniformly and stably enter the grain boundary, and between the two heat-treatment stages, water washing, water quenching, etc. can be carried out.
[0040] In S3, the product obtained in step S2 is roasted once or twice in air or a reducing atmosphere to obtain a catalyst having precious metals supported on the grain boundaries and surfaces of rare earth manganese zirconium composite oxide and / or alumina. The amount of precious metal G supported in the catalyst is 0.01% to 2%, preferably 0.1% to 1%, in mass percentage. The reducing atmosphere contains one or more of CO and H2. The roasting temperature is 400 to 850°C, and the roasting time is 0.5h to 24h, preferably 450 to 750°C, and the roasting time is 1h to 12h. The catalyst having precious metals supported on the grain boundaries and surfaces obtained above is roasted once or twice to obtain a catalyst material with a specific structure, and after roasting once, surface treatment can be performed to avoid two sintering and aggregation.
[0041] In the above embodiment, when performing the heat treatment in step S2, the grain boundaries of the rare earth manganese zirconium composite oxide and / or alumina can be activated to form a channel for the diffusion of the precious metal by controlling the appropriate temperature, and the depth and distribution of the precious metal along the grain boundaries can be controlled by controlling the heat treatment time. In step S3, the precious metal at the grain boundaries or surface can be reduced or partially reduced by controlling the air or reducing atmosphere, the reduction temperature, and the reduction time. The precious metal is distributed at the grain boundaries and surface of the rare earth manganese zirconium composite oxide and / or aluminum oxide by steps S2 and S3 to form a multiphase interface, which has a larger steric hindrance and a stronger anchoring effect, suppresses the high-temperature migration, aggregation, and growth of the precious metal, improves the high-temperature stability of the precious metal, and reduces the amount of precious metal used. In addition, the multiphase interface has a synergistic catalytic effect, which reduces the lattice oxygen activation energy and increases the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.
[0042] The embodiment of the present invention further provides a method for manufacturing a honeycomb-type precious metal catalyst, as in the above embodiment, in which the honeycomb-type precious metal catalyst is coated with one or more coating materials in a hierarchical or compartmental manner, the coating materials being alumina, rare earth manganese zirconium composite oxide, alumina with precious metal supported on grain boundaries and surfaces, rare earth manganese zirconium composite oxide with precious metal supported on grain boundaries and surfaces, or a mixture of rare earth manganese zirconium composite oxide and alumina with precious metal supported on grain boundaries and surfaces, the flow chart of the method is shown in FIG. 2, and the manufacturing steps include A1 to A3.
[0043] In A1, the one or more coating materials, adhesive, acidity regulator and water are uniformly mixed in one or multiple steps to prepare a coating slurry.
[0044] In step A2, the coating slurry obtained in step A1 is coated on a honeycomb carrier in one or multiple steps, or coated on the honeycomb carrier in a sectioned or layered manner, and then dried. The honeycomb carrier may be made of porous ceramics or metal. The drying temperature is 50-200°C, and the drying time is 1h-48h.
[0045] In step A3, the product obtained in step A2 is heat-treated or / and roasted in air or a reducing atmosphere to obtain a catalyst with precious metals supported on the honeycomb grain boundaries and surfaces. The amount of precious metal G supported in the catalyst is 0.03-2.0 g / L, preferably 0.15-1.5 g / L. The heat treatment temperature is 200-750°C, the time is 0.5h-24h, the heat treatment temperature is preferably 400-700°C, and the heat treatment time is preferably 1h-12h. In order to meet the special requirements for the performance of honeycomb-type precious metal catalysts for different applications, it is necessary to adjust or change the microstructure of the catalyst, and therefore it is necessary to adopt different heat treatment regimes, for example, to perform heat treatment in stages to make more precious metals more uniformly and stably enter the grain boundaries, and treatments such as water washing and water quenching can be performed between the two heat treatment stages. The roasting temperature is 400-850°C, and the roasting time is 0.5h-24h, preferably, the roasting temperature is 450-750°C, and the roasting time is 1h-12h. The honeycomb-type precious metal catalyst obtained above is roasted once or twice to obtain a catalyst with a specific structure, and after roasting once, the surface treatment can be performed to avoid two sintering and aggregation.
[0046] The embodiment of the present invention further provides a method for manufacturing a honeycomb-type precious metal catalyst, similar to the honeycomb-type precious metal catalyst provided by the above embodiment, by uniformly mixing rare earth manganese zirconium composite oxide and / or alumina, liquid salt of precious metal G, acidity regulator, adhesive and water in one or multiple steps to prepare a coating slurry, coating the slurry on a honeycomb carrier in one or multiple steps, or coating the honeycomb carrier in sections or layers, and drying, and then heat-treating or / and roasting the dried honeycomb carrier in a reducing atmosphere to obtain a catalyst with precious metal supported on the honeycomb-type grain boundaries and surfaces.
[0047] The embodiments of the present invention provide a catalyst with precious metal supported on grain boundaries and surfaces and a honeycomb-type precious metal catalyst, respectively, in which the precious metal is dispersed on the grain boundaries and surfaces of alumina and / or rare earth manganese zirconium composite oxide to form a multi-phase interface, which has greater steric hindrance and stronger anchoring effect, inhibits the high-temperature migration, aggregation and growth of the precious metal, improves the high-temperature stability and catalytic performance of the precious metal, and reduces the amount of precious metal used. The multi-phase interface also has a synergistic catalytic effect, which can reduce the lattice oxygen activation energy and increase the amount of active oxygen, thereby improving the NO oxidation rate and low-temperature catalytic activity.
[0048] The embodiments of the present invention further provide applications of the above-mentioned grain boundary and surface supported precious metal catalysts and honeycomb-type precious metal catalysts in the fields of automobile exhaust gas purification, industrial exhaust gas treatment, natural gas catalytic combustion, petrochemistry, hydrogen energy, and batteries. The grain boundary and surface supported precious metal catalysts and honeycomb-type precious metal catalysts provided by the embodiments of the present invention have excellent NO oxidation low-temperature catalytic activity and high-temperature stability, and can meet the application requirements of various related fields.
[0049] The present invention will now be further described with reference to specific examples.
[0050] Comparative Example 1 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 The mixture was homogeneously mixed with the solid powder of O2, then dried at a temperature of 120 °C for 10 h, and then roasted at 700 °C for 3 h in an air atmosphere to form a catalyst Pt (0.2 wt%) / Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 The catalyst performance test was carried out on the above catalyst, and the maximum conversion rate of NO was 63.52%, the temperature corresponding to the maximum conversion rate of NO was 326 ° C, and the maximum conversion rate of NO of the catalyst after hydrothermal aging at 650 ° C / 10% H2O / 100 h was 49.38%.
[0051] Comparative Example 2 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.2wt%) / Ce(0.2wt%), then dried at 100°C for 6h, and then roasted at 600°C for 6h in an air atmosphere to obtain the catalyst Pt(0.2wt%) / Ce .... 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The catalytic performance test was carried out on the above catalysts, and the maximum conversion rate of NO was 64.06%, the temperature corresponding to the maximum conversion rate of NO was 324°C, and the maximum conversion rate of NO of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 50.37%.
[0052] Comparative Example 3 A certain volume of platinum nitrate liquid salt was weighed out with a loading of Pt (1.1 g / L), followed by Al2O3, Ce, 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99 Add the acidity regulator and water to uniformly mix with platinum nitrate liquid salt, then add adhesive and mix uniformly to prepare a slurry, which is then applied to a cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, and roasted at 600°C for 3 hours in a H2 reducing atmosphere to obtain a honeycomb-type precious metal catalyst Pt(1.1g / L) / Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99 -Al2O3 was obtained. The catalytic performance test was carried out on the above catalyst, and the maximum conversion rate of NO was 65.54%, and the corresponding temperature for the maximum conversion rate of NO was 330°C. After hydrothermal aging at 650°C / 10% H2O / 100h, the maximum conversion rate of NO of the catalyst was 50.93%.
[0053] Example 1 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.10 Mn 0.05 Y 0.05 Zr 0.80 The mixture was homogeneously mixed with the solid powder of O2, then dried at 120 °C for 10 h, heat-treated at 500 °C for 3 h, and roasted at 700 °C for 3 h in a H2 reducing atmosphere. 0.10 Mn 0.05 Y 0.05 Zr 0.80 O2 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 71.44%, the temperature corresponding to the maximum NO conversion rate was 283°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 60.13%.
[0054] Example 2 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.2wt%) / Ce(II) and dried at 100℃ for 6h, then heat-treated at 200℃ for 6h, heat-treated at 500℃ for 2h, and roasted at 600℃ for 6h in a H2 reducing atmosphere to obtain the catalyst Pt(0.2wt%) / Ce(II) 0.20 Mn 0.05 Pr 0.05 Zr 0.70 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 75.52%, the temperature corresponding to the maximum NO conversion rate was 273°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 65.31%.
[0055] Example 3 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.10 Yb 0.10 Zr 0.60 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.2wt%) / Ce(0.2wt%), dried at 110℃ for 12h, heat-treated at 530℃ for 3h, and roasted at 650℃ for 3h in a H2 reducing atmosphere to obtain the catalyst Pt(0.2wt%) / Ce(0.2wt%) / Ce(0.2wt%). 0.20 Mn 0.10 Yb 0.10 Zr 0.60 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 73.54%, the temperature corresponding to the maximum NO conversion rate was 277°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 63.54%.
[0056] Example 4 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.10 Gd 0.20 Zr 0.50 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.2wt%) / Ce(0.2wt%), dried at 90℃ for 23h, heat-treated at 530℃ for 3h, and roasted at 650℃ for 3h to obtain the catalyst Pt(0.2wt%) / Ce(0.2wt%) / Ce(0.2wt%). 0.20 Mn 0.10 Gd 0.20 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 74.78%, the temperature corresponding to the maximum NO conversion rate was 273°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 64.43%.
[0057] Example 5 A certain volume of chloroplatinic acid solution with a Pt loading of 0.3 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.15 EU 0.15 Zr 0.50 O 1.99 The mixture was mixed uniformly with the solid powder of Ce, washed, and then dried at 100°C for 13 h, heat-treated at 530°C for 3 h, and roasted at 650°C for 3 h in a H2 reducing atmosphere to obtain the catalyst Pt(0.3wt%) / Ce 0.20 Mn 0.15 EU 0.15 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 76.63%, the temperature corresponding to the maximum NO conversion rate was 267°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 65.16%.
[0058] Example 6 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.4 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.15 La 0.15 Zr 0.50 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.4wt%) / Ce(0.4wt%), dried at 80℃ for 9h, then heat-treated at 300℃ for 5h, heat-treated at 550℃ for 3h, and roasted at 650℃ for 5h in H2 reducing atmosphere to obtain the catalyst Pt(0.4wt%) / Ce(0.4wt%) / Ce(0.4wt%). 0.20 Mn 0.15 La 0.15 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 77.33%, the temperature corresponding to the maximum NO conversion rate was 261°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 66.46%.
[0059] Example 7 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.4 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.15 Nd 0.15 Zr 0.50 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.4wt%) / Ce(0.4wt%), dried at 110℃ for 15h, heat-treated at 550℃ for 2h, and roasted at 650℃ for 5h in H2 reducing atmosphere to obtain the catalyst Pt(0.4wt%) / Ce(0.4wt%) / Ce(0.4wt%). 0.20 Mn 0.15 Nd 0.15 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 77.34%, the temperature corresponding to the maximum NO conversion rate was 266°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 66.68%.
[0060] Example 8 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.4 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.15 La 0.15 Zr 0.50 O 1.99 The mixture was mixed uniformly with the solid powder of Pt(0.4wt%) / Ce(0.4wt%), dried at 90℃ for 10h, heat-treated at 550℃ for 2h, and roasted at 650℃ for 5h in H2 reducing atmosphere to obtain the catalyst Pt(0.4wt%) / Ce(0.4wt%) / Ce(0.4wt%). 0.20 Mn 0.15 La 0.15 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 76.91%, the temperature corresponding to the maximum NO conversion rate was 267°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 65.33%.
[0061] Example 9 A certain volume of palladium nitrate liquid salt with a Pd loading of 0.4 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The mixture was mixed uniformly with the solid powder of Pd(0.4wt%) / Ce(0.5wt%), dried at 100℃ for 24h, heat-treated at 550℃ for 2h, and roasted at 650℃ for 5h in H2 reducing atmosphere to obtain the catalyst Pd(0.4wt%) / Ce(0.5wt%) / Ce(0.5wt%). 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The precious metal Pd was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 74.74%, the temperature corresponding to the maximum NO conversion rate was 270°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 63.16%.
[0062] Example 10 A certain volume of platinum acetate liquid salt with a Pt loading of 0.4 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The mixture was mixed uniformly with the solid powder of Ce, dried at 90°C for 20 h, heat-treated at 550°C for 6 h, and roasted at 650°C for 5 h in a H2 reducing atmosphere to obtain the catalyst Pt(0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 77.78%, the temperature corresponding to the maximum NO conversion rate was 266°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 64.37%.
[0063] Example 11 0.4wt% Pt 0.5 Pd 0.5 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of support, and the rare earth manganese zirconium composite oxide Ce was 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.90 N 0.10 The mixture was mixed uniformly with the solid powder of 100°C, dried at 100°C for 12 hours, heat-treated at 450°C for 6 hours, and roasted at 600°C for 6 hours in a H2 reducing atmosphere to obtain the catalyst Pt 0.5 Pd 0.5 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.90 N 0.10 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 78.13%, the temperature corresponding to the maximum NO conversion rate was 261°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 68.49%.
[0064] Example 12 A certain volume of platinum nitrate and palladium nitrate liquid salt with a Pt0.67Pd0.33 alloy loading of 0.4 wt% was weighed out, and the rare earth manganese zirconium composite oxide Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02The mixture was mixed uniformly with the solid powder of 100°C, dried at 100°C for 20 h, heat-treated at 450°C for 6 h, and roasted at 600°C for 8 h in a H2 reducing atmosphere to obtain the catalyst Pt 0.67 Pd 0.33 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 80.30%, the temperature corresponding to the maximum NO conversion rate was 242°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 73.11%.
[0065] (Example 13) 0.4wt% Pt 0.67 Pd 0.33 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of alloy supported, and a rare earth manganese zirconium composite oxide Ce with an element gradient distribution structure was prepared. 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The mixture was dried at 100°C for 20 h, then heat-treated at 500°C for 8 h, and roasted at 550°C for 5 h in a H2 reducing atmosphere to obtain the catalyst Pt 0.67 Pd 0.33 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 N 0.02 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 81.43%, the temperature corresponding to the maximum NO conversion rate was 236°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 76.66%.
[0066] Example 14 0.4wt% Pt 0.75 Pd 0.25 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of support, and the rare earth manganese zirconium composite oxide Ce was 0.20 Mn 0.20 La 0.05 Nd 0.05 Zr 0.50 O 1.98 P 0.02 The mixture was mixed uniformly with the solid powder of 100% ZnO, dried at 90°C for 24 h, heat-treated at 450°C for 6 h, and roasted at 600°C for 8 h in a H2 reducing atmosphere to obtain the catalyst Pt 0.75 Pd 0.25 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Nd 0.05 Zr 0.50 O 1.98 P 0.02 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.38%, the temperature corresponding to the maximum NO conversion rate was 253°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 70.16%.
[0067] Example 15 0.4wt% Pt 0.91 Pd 0.09 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of alloy supported, and the rare earth manganese zirconium composite oxide Ce was 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58 The mixture was homogeneously mixed with the solid powder of O2, dried at 120℃ for 6h, heat-treated at 450℃ for 6h, and roasted at 600℃ for 8h in a H2 reducing atmosphere. 0.91 Pd 0.09 (0.4wt%) / Ce 0.14 Mn 0.16 La 0.03 Nd 0.04 Y0.05 Zr 0.58 O2 was obtained. The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 80.63%, the temperature corresponding to the maximum NO conversion rate was 241°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 74.36%.
[0068] (Example 16) 0.4wt% Pt 0.83 Pd 0.17 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of alloy supported, and the rare earth manganese zirconium composite oxide Ce was 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 F 0.02 The mixture was mixed uniformly with the solid powder of 100% 1,0 ... 0.83 Pd 0.17 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zr 0.50 O 1.98 F 0.02 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.43%, the temperature corresponding to the maximum NO conversion rate was 246°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 71.67%.
[0069] (Example 17) 0.4wt% Pt 0.91 Pd 0.09 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of support, and the rare earth manganese zirconium composite oxide Ce was 0.20 Mn 0.20 La 0.02 Nd 0.03 Y0.03 Cu 0.02 Zr 0.50 O 1.98 The solid powder was mixed uniformly, dried at 150°C for 10 h, heat-treated at 450°C for 6 h, and roasted at 600°C for 8 h in a H2 reducing atmosphere to obtain the catalyst Pt 0.91 Pd 0.09 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.98 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 82.39%, the temperature corresponding to the maximum NO conversion rate was 236°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 76.88%.
[0070] (Example 18) 0.4wt% Pt 0.91 Pd 0.09 A certain volume of platinum nitrate and palladium nitrate liquid salt was weighed out based on the amount of alloy supported, and a rare earth manganese zirconium composite oxide with a core-shell structure, Ce, was prepared. 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58 The mixture was homogeneously mixed with O2 solid powder, dried at 110℃ for 7h, heat-treated at 460℃ for 5h, and roasted at 550℃ for 5h in H2 reducing atmosphere. 0.91 Pd 0.09 (0.4wt%) / Ce 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58O2 was obtained. The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 81.98%, the temperature corresponding to the maximum NO conversion rate was 234°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 77.33%.
[0071] (Example 19) A certain amount of Pt 0.91 Pd 0.09 (0.4wt%) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.98 The catalyst was taken, and then the adhesive, acidity regulator, and water were added and mixed uniformly to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier, dried at 100°C for 4 hours, and then roasted at 550°C for 5 hours in an air atmosphere to obtain the honeycomb-type precious metal catalyst Pt 0.91 Pd 0.09 (0.35g / L) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Y 0.03 Cu 0.02 Zr 0.50 O 1.99 The precious metals Pt and Pd were dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 83.86%, the temperature corresponding to the maximum NO conversion rate was 230°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 75.1%.
[0072] (Example 20) A certain volume of platinum nitrate liquid salt with a Pt loading of 0.6 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.20 La 0.02 Nd 0.03 Sm 0.03 Y 0.02Zr 0.50 O 1.98 The solid powder was mixed uniformly, dried at 60°C for 32 h, heat-treated at 400°C for 9 h, and roasted at 550°C for 9 h in a H2 reducing atmosphere to obtain the catalyst Pt(0.6wt%) / Ce 0.20 Mn 0.20 La 0.02 Nd 0.03 Sm 0.03 Y 0.02 Zr 0.50 O 1.98 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 80.36%, the temperature corresponding to the maximum NO conversion rate was 245°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 70.43%.
[0073] Example 21 A certain volume of platinum nitrate liquid salt with a Pt loading of 0.8 wt% was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.20 Mn 0.30 La 0.02 Co 0.03 Y 0.05 Zr 0.40 O 1.98 The solid powder was mixed uniformly, dried at 100°C for 6 h, heat-treated at 400°C for 9 h, and roasted at 550°C for 12 h in a H2 reducing atmosphere to obtain the catalyst Pt(0.8wt%) / Ce 0.20 Mn 0.30 La 0.02 Co 0.03 Y 0.05 Zr 0.40 O 1.98 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 78.36%, the temperature corresponding to the maximum NO conversion rate was 246°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 68.41%.
[0074] Example 22 A certain volume of ruthenium nitrate liquid salt with 0.1 wt% Ru loading was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.40 Mn 0.05 La 0.05 Sr 0.05 Sc 0.05 Zr 0.40 O 1.98 The mixture was mixed with the solid powder uniformly, dried at 80°C for 30 h, heat-treated at 700°C for 1 h, and roasted at 750°C for 9 h in a CO reducing atmosphere to obtain the catalyst Ru(0.1wt%) / Ce 0.40 Mn 0.05 La 0.05 Sr 0.05 Sc 0.05 Zr 0.40 O 1.98 The precious metal Ru was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 69.16%, the corresponding temperature for the maximum NO conversion rate was 276°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 59.38%.
[0075] (Example 23) A certain volume of ruthenium nitrate liquid salt with 0.1 wt% Ru loading was weighed out and mixed with rare earth manganese zirconium oxide Ce. 0.40 Mn 0.05 La 0.05 Sr 0.05 Sc 0.05 Zr 0.40 O 1.98 The mixture was mixed with the solid powder uniformly, dried at 90℃ for 15 h, heat-treated at 300℃ for 4 h, heat-treated at 700℃ for 3 h, and roasted at 750℃ for 6 h in a CO reducing atmosphere to obtain the catalyst Ru(0.1wt%) / Ce 0.40 Mn 0.05 La 0.05 Sr 0.05 Sc 0.05 Zr 0.40 O 1.98The precious metal Ru was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 70.02%, the temperature corresponding to the maximum NO conversion rate was 271°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 60.16%.
[0076] Example 24 A certain volume of iridium nitrate liquid salt with 0.1 wt% Ir loading was weighed out and 0.40 Mn 0.05 La 0.05 Ba 0.05 Al 0.05 Zr 0.40 O 1.98 The solid powder was mixed uniformly, dried at 120°C for 5 h, heat-treated at 600°C for 9 h, and roasted at 750°C for 6 h in a H2 reducing atmosphere to obtain the catalyst Ir(0.1wt%) / Ce 0.40 Mn 0.05 La 0.05 Ba 0.05 Al 0.05 Zr 0.40 O 1.98 The precious metal Ir was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 68.11%, the temperature corresponding to the maximum NO conversion rate was 279°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 56.9%.
[0077] (Example 25) A certain volume of osmium acetate liquid salt with 0.01 wt% Os loading was weighed out and 0.40 Mn 0.05 La 0.05 Hf 0.05 Ni 0.05 Zr 0.40 O 1.98 The mixture was mixed with the solid powder uniformly, dried at 160°C for 1 h, heat-treated at 750°C for 0.5 h, and roasted at 800°C for 1 h in a H2 reducing atmosphere to obtain the catalyst Os(0.01wt%) / Ce 0.40 Mn 0.05 La 0.05 Hf0.05 Ni 0.05 Zr 0.40 O 1.98 The precious metal Os was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 66.39%, the temperature corresponding to the maximum NO conversion rate was 286°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 53.83%.
[0078] (Example 26) A certain volume of platinum nitrate liquid salt with a Pt loading of 0.8 wt% was weighed out and mixed with 30 g of Ce. 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.40 O 1.98 and 70g of alumina solid powder were mixed uniformly, dried at 90℃ for 6h, heat-treated at 400℃ for 9h, and roasted at 550℃ for 9h in H2 reducing atmosphere to obtain the catalyst Pt(0.8wt%) / Ce 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.40 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.93%, the temperature corresponding to the maximum NO conversion rate was 243°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 70.53%.
[0079] Example 27 A certain amount of Pt(0.8wt%) / Ce prepared in Example 22 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.40 O 1.98The -Al2O3 catalyst is taken, and then adhesive, acidity regulator, water, etc. are added and mixed uniformly to prepare a slurry, which is then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb is then dried at 100°C for 4 hours, and roasted at 600°C for 1 hour in an air atmosphere to obtain a honeycomb-type precious metal catalyst Pt(0.5g / L) / Ce 0.20 Mn 0.30 La 0.05 Y 0.05 Zr 0.40 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 81.69%, the corresponding temperature for the maximum NO conversion rate was 241℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 73.18%.
[0080] (Example 28) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.0 wt% was weighed out and mixed with 40 g of Ce. 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.98 and 60g of alumina solid powder were mixed uniformly, dried at 130℃ for 2h, heat-treated at 450℃ for 12h, and roasted at 700℃ for 7h in H2 reducing atmosphere to obtain the catalyst Pt(1.0wt%) / Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 78.61%, the temperature corresponding to the maximum NO conversion rate was 253°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 66.84%.
[0081] (Example 29) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.0 wt% was weighed out and mixed with 50 g of Ce. 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 and 50g of alumina solid powder were mixed uniformly, dried at 140℃ for 5h, heat-treated at 450℃ for 12h, and roasted at 700℃ for 8h in H2 reducing atmosphere to obtain the catalyst Pt(1.0wt%) / Ce 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 77.36%, the corresponding temperature for the maximum NO conversion rate was 256°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 65.18%.
[0082] (Example 30) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.0 wt% was weighed out and mixed with 60 g of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Ti 0.20 Zr 0.20 O 1.98 and 40g of alumina solid powder were mixed uniformly, dried at 80℃ for 9h, heat-treated at 450℃ for 12h, and roasted at 700℃ for 7h in H2 reducing atmosphere to obtain the catalyst Pt(1.0wt%) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 Ti 0.20 Zr 0.20 O 1.98-Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 77.7%, the temperature corresponding to the maximum NO conversion rate was 272°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 66.79%.
[0083] (Example 31) A certain volume of platinum nitrate liquid salt with a Pt loading of 2.0 wt% was weighed out and mixed with 70 g of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 and 30g of alumina solid powder were mixed uniformly, dried at 200℃ for 1h, heat-treated at 600℃ for 6h, and roasted at 700℃ for 9h in H2 reducing atmosphere to obtain the catalyst Pt(2.0wt%) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 78.6%, the temperature corresponding to the maximum NO conversion rate was 269°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 67.46%.
[0084] Example 32 A certain volume of platinum nitrate liquid salt with a Pt loading of 2.0 wt% was weighed out and mixed with 30 g of alumina and 70 g of Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98The solid powder was mixed uniformly, dried at 200°C for 1 h, then heat-treated at 230°C for 6 h, heat-treated at 630°C for 4 h, and roasted at 700°C for 5 h in a H2 reducing atmosphere to obtain the catalyst Pt(2.0wt%) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.96%, the temperature corresponding to the maximum NO conversion rate was 261°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 68.41%.
[0085] (Example 33) A certain volume of rhodium nitrate liquid salt with 0.5wt% Rh loading was weighed out and 80g of Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 Nb 0.05 Zr 0.40 O 1.98 and 20g of alumina solid powder were mixed uniformly, dried at 50℃ for 48h, heat-treated at 300℃ for 3h, and roasted at 850℃ for 0.5h in H2 reducing atmosphere to obtain catalyst Rh(0.5wt%) / Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 Nb 0.05 Zr 0.40 O 1.98 -Al2O3 was obtained. The precious metal Rh was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 73.43%, the corresponding temperature for the maximum NO conversion rate was 269°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 61.53%.
[0086] (Example 34) A certain volume of silver citrate liquid salt with 0.5 wt% Ag loading was weighed out and 90 g of Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 S 0.05 Zr 0.40 O 1.98 and 10g of alumina solid powder were mixed uniformly, dried at 160℃ for 4h, heat-treated at 600℃ for 9h, and roasted at 750℃ for 6h in H2 reducing atmosphere to obtain the catalyst Ag(0.5wt%) / Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 S 0.05 Zr 0.40 O 1.98 -Al2O3 was obtained. The precious metal Ag was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 70.93%, the corresponding temperature for the maximum NO conversion rate was 270℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 60.37%.
[0087] Example 35 A certain volume of chloroauric acid liquid salt with 0.5 wt% Au loading was weighed out, and 90 g of Ce was added. 0.40 Mn 0.05 La 0.05 Nd 0.05 Fe 0.05 Zr 0.40 O 1.98 and 10g of alumina solid powder were mixed uniformly, washed, and then dried at 100°C for 8h, heat-treated at 200°C for 24h, and roasted at 400°C for 24h in a H2 reducing atmosphere to obtain the catalyst Au(0.5wt%) / Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 Fe 0.05 Zr 0.40 O 1.98-Al2O3 was obtained. The precious metal Au was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 71.34%, the temperature corresponding to the maximum NO conversion rate was 281°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 60.66%.
[0088] (Example 36) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.0 wt% was weighed out and mixed uniformly with alumina solid powder, dried at a temperature of 50°C for 6 h, then heat-treated at 450°C for 12 h, and roasted at 700°C for 7 h in a H2 reducing atmosphere to obtain a catalyst Pt (1.0 wt%) / Al2O3. The precious metal Pt was dispersed on the grain boundaries and surface of alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 70.96%, the corresponding temperature for the maximum NO conversion rate was 283°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 60.31%.
[0089] (Example 37) A certain amount of Pt(1.0wt%) / Al2O3 catalyst prepared in Example 31 was taken, and then adhesive, acidity regulator, water, etc. were added and mixed uniformly to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier, and then dried at 110℃ for 5h, and then the honeycomb carrier was roasted at 450℃ for 6h in air atmosphere to obtain a honeycomb-type precious metal catalyst Pt(0.03g / L) / Al2O3, in which the precious metal Pt was dispersed on the grain boundary and surface of alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 68.33%, the temperature corresponding to the maximum NO conversion rate was 279℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 60.93%.
[0090] (Example 38) A certain volume of platinum nitrate liquid salt with a Pt loading of 0.2 wt% was weighed out and 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99The solid powder was mixed uniformly, dried at 110°C for 12 h, and then heat-treated at 530°C for 8 h and roasted at 650°C for 3 h in a H2 reducing atmosphere to obtain the catalyst Pt(0.2wt%) / Ce 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 76.49%, the temperature corresponding to the maximum NO conversion rate was 270°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 63.31%.
[0091] (Example 39) A certain amount of Pt(0.2wt%) / Ce prepared in Example 33 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99 The catalyst was taken, and then adhesive, acidity regulator, water, etc. were added and mixed uniformly to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier, dried at 130°C for 6 hours, and then roasted at 500°C for 3 hours in an air atmosphere to obtain a honeycomb-type precious metal catalyst Pt(0.15g / L) / Ce 0.20 Mn 0.15 Y 0.15 Zr 0.50 O 1.99 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 76.43%, the corresponding temperature for the maximum NO conversion rate was 266°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 65.13%.
[0092] (Example 40) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.1 g / L was weighed out and 0.20 Mn 0.20 La 0.05 Nd 0.05 W 0.05 Zr 0.50 O 1.98N 0.02 Add the acidity regulator, water, etc. and mix uniformly, then add the adhesive and mix uniformly to prepare a slurry, which is then applied to a cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, heat-treated at a low temperature of 310°C for 8 hours, heat-treated at a high temperature of 730°C for 2 hours, and roasted at 800°C for 3 hours in a H2 reducing atmosphere to obtain a honeycomb-type precious metal catalyst Pt(1.1g / L) / Ce 0.20 Mn 0.20 La 0.05 Nd 0.05 W 0.05 Zr 0.50 O 1.98 N 0.02 The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 77.71%, the corresponding temperature for the maximum NO conversion rate was 256°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 66.73%.
[0093] (Example 41) A certain volume of platinum nitrate liquid salt was weighed out with a Pt (1.1 g / L) loading, and Al2O3, Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99 Add the acidity regulator, water, etc. and mix uniformly, then add the adhesive and mix uniformly to prepare a slurry, which is then applied to a cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, heat-treated at 400°C for 8 hours, and roasted at 600°C for 3 hours in a H2 reducing atmosphere to obtain a honeycomb-type precious metal catalyst Pt(1.1g / L) / Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 W 0.05 Zr 0.30 O 1.99-Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.17%, the corresponding temperature for the maximum NO conversion rate was 236℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 68.37%.
[0094] (Example 42) A certain volume of platinum nitrate liquid salt was weighed out with a Pt (1.1 g / L) loading, and Al2O3, Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 Y 0.05 Zr 0.30 O 1.99 Add the acidity regulator, water, etc. and mix uniformly. Here, Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 Y 0.05 Zr 0.30 O 1.99 The adhesive is then added and mixed uniformly to prepare a slurry, which is then applied to the cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, heat-treated at 500°C for 8 hours, and roasted at 550°C for 5 hours in a H2 reducing atmosphere to obtain the honeycomb-type precious metal catalyst Pt(1.1g / L) / Ce 0.30 Mn 0.25 La 0.05 Nd 0.05 Y 0.05 Zr 0.30 O 1.99 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 80.11%, the corresponding temperature for the maximum NO conversion rate was 234℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 69.83%.
[0095] (Example 43) A certain volume of platinum nitrate liquid salt was weighed out with the loading amount of Pt (1.5g / L), and Al2O3, acidity regulator, water, etc. were added and mixed uniformly, and then adhesive was added and mixed uniformly to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier, dried at 150℃ for 3h, then heat-treated at 500℃ for 6h, and roasted at 550℃ for 2h in H2 reducing atmosphere to obtain a honeycomb-type precious metal catalyst Pt(1.5g / L) / Al2O3, with the precious metal Pt dispersed on the grain boundary and surface of alumina. The catalytic performance test was carried out on the above catalyst, and the maximum conversion rate of NO was 72.36%, the temperature corresponding to the maximum conversion rate of NO was 266℃, and the maximum conversion rate of the catalyst NO after hydrothermal aging at 650℃ / 10%H2O / 100h was 62.11%.
[0096] (Example 44) A certain volume of platinum nitrate liquid salt with a Pt loading of 2.0 g / L was weighed out and 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 , acidity regulator, water, etc. are mixed uniformly, and then adhesive is added and mixed uniformly to prepare a slurry, which is then applied to a cordierite ceramic honeycomb carrier, dried at 100°C for 4 hours, heat-treated at 380°C for 7 hours, and roasted at 500°C for 4 hours in a H2 reducing atmosphere. Al2O3, adhesive, acidity regulator, water, etc. are mixed to prepare a slurry, which is then applied to the roasted cordierite ceramic honeycomb carrier, dried at 90°C for 3 hours, and roasted at 450°C for 8 hours to prepare a honeycomb-type precious metal catalyst Pt(2.0g / L) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 81.19%, the corresponding temperature for the maximum NO conversion rate was 239℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 70.19%.
[0097] (Example 45) A certain volume of platinum nitrate liquid salt with a loading of Pt (1.3 g / L) was weighed out and mixed uniformly with Al2O3, acidity regulator, water, etc., and then an adhesive was added and mixed uniformly to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 120°C for 4 hours, heat-treated at 430°C for 5 hours, and roasted at 500°C for 7 hours in a H2 reducing atmosphere, followed by heating at 100°C for 10 hours. 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 The mixture is mixed with the binder, the acidity regulator, water, etc. to prepare a slurry, which is then applied to the calcined cordierite ceramic honeycomb carrier, dried at 90°C for 3 hours, and then calcined in an air atmosphere at 450°C for 2 hours to obtain a honeycomb-type precious metal catalyst Pt(1.3g / L) / Ce 0.30 Mn 0.30 La 0.05 Cu 0.05 Zr 0.30 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 80.60%, the corresponding temperature for the maximum NO conversion rate was 233°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 69.33%.
[0098] (Example 46) A certain volume of platinum nitrate liquid salt with a loading of Pt (1.5g / L) is weighed out, uniformly mixed with Al2O3, acidity regulator, water, etc., and then an adhesive is added and mixed uniformly to prepare a slurry, which is then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb carrier is then dried at 90°C for 3 hours, heat-treated at a low temperature of 340°C for 5 hours, heat-treated at a high temperature of 560°C for 3 hours, and roasted at 650°C for 5 hours in a H2 reducing atmosphere. Then, Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 Fe 0.05 Zr0.40 O 1.98 The mixture is mixed with the binder, the acidity regulator, water, etc. to prepare a slurry, which is then applied to the calcined cordierite ceramic honeycomb carrier, dried at 100°C for 5 hours, and then calcined in an air atmosphere at 510°C for 2 hours to obtain a honeycomb-type precious metal catalyst Pt(1.5g / L) / Ce 0.40 Mn 0.05 La 0.05 Nd 0.05 Fe 0.05 Zr 0.40 O 1.98 The precious metal Pt was dispersed on the grain boundaries and surface of the alumina. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.60%, the corresponding temperature for the maximum NO conversion rate was 243°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 69.81%.
[0099] (Example 47) A certain volume of platinum nitrate liquid salt with a Pt loading of 2.0 g / L was weighed out, half of the platinum nitrate liquid salt was taken out, and an appropriate amount of Ce was added. 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98 , acidity adjuster, water, etc., and then add adhesive and mix uniformly to prepare coating slurry, which is then coated on cordierite ceramic honeycomb carrier, dried at 110°C for 6 hours, heat-treated at 500°C for 6 hours, and roasted at 700°C for 3 hours in H2 reducing atmosphere. Then, the remaining half of the platinum nitrate liquid salt is taken out and mixed with an appropriate amount of Al2O3 powder, acidity adjuster, water, etc. to prepare coating slurry, which is then coated on the roasted cordierite ceramic honeycomb carrier, dried at 90°C for 3 hours, heat-treated at 560°C for 4 hours, and roasted at 500°C for 7 hours in H2 reducing atmosphere to prepare honeycomb-type precious metal catalyst Pt(2.0g / L) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 V 0.20 Zr 0.20 O 1.98-Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 82.96%, the corresponding temperature for the maximum NO conversion rate was 236℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 70.16%.
[0100] (Example 48) A certain volume of platinum nitrate liquid salt with a loading of Pt (1.0 g / L) was weighed out, and 20 g of Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98 1. Mix 70g of alumina, acidity regulator, water, etc. evenly, add adhesive and mix evenly, prepare slurry, and apply it to cordierite ceramic honeycomb carrier, dry at 80℃ for 13h, heat-treat at 330℃ for 8h, and roast at 550℃ for 4h in H2 reducing atmosphere, then weigh out 10g of alumina, mix it evenly with adhesive, acidity regulator, water, etc., prepare slurry, and apply it to the roasted cordierite ceramic honeycomb carrier, dry at 90℃ for 3h, and roast at 600℃ in air atmosphere for 1h to prepare honeycomb-type precious metal catalyst Pt(1.0g / L) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.31%, the corresponding temperature for the maximum NO conversion rate was 256℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 68.69%.
[0101] (Example 49) 40g of Al2O3 was weighed out and mixed uniformly with acidity regulator, adhesive and water to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 120°C for 4h and roasted at 500°C for 7h in air. Then, a certain volume of platinum nitrate liquid salt with a loading amount of Pt (1.4g / L) was weighed out, and 40g of Ce was added. 0.30 Mn 0.20 La 0.10 Cu 0.10 Zr 0.30 O 1.98 20g of Al2O3, acidity regulator, water, etc. are mixed uniformly, and then an adhesive is added and mixed uniformly to prepare a slurry, which is then applied to the calcined cordierite ceramic honeycomb carrier, dried at 90°C for 3h, heat-treated at 430°C for 5h, and calcined in a hydrogen atmosphere at 550°C for 3h to obtain a honeycomb-type precious metal catalyst Pt(1.4g / L) / Ce 0.30 Mn 0.20 La 0.10 Cu 0.10 Zr 0.30 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.33%, the corresponding temperature for the maximum NO conversion rate was 238℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 68.16%.
[0102] (Example 50) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.0 g / L was weighed out and uniformly mixed with 50 g of alumina solid powder, acidity regulator, adhesive, water, etc. to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at a temperature of 90°C for 8 hours, heat-treated at 460°C for 5 hours, and roasted at 550°C for 9 hours in a H2 reducing atmosphere. Then, 50 g of Ce with a core-shell structure was added to the honeycomb carrier. 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58The O2 was weighed and mixed uniformly with adhesive, acidity regulator, water, etc. to prepare a slurry, which was then applied to the calcined cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, and calcined in an air atmosphere at 460°C for 6 hours to obtain a honeycomb-type precious metal catalyst Pt(1.0g / L) / Ce 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58 O2-Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 81.96%, the corresponding temperature for the maximum NO conversion rate was 246°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 70.19%.
[0103] (Example 51) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.0 wt% was weighed out and mixed with 40 g of Ce. 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.98 The solid powder was mixed uniformly, dried at 80°C for 9 h, heat-treated at 410°C for 6 h, and roasted at 560°C for 7 h in a H2 reducing atmosphere to obtain the catalyst Pt(1.0wt%) / Ce 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.9 The above catalyst was uniformly mixed with an acidity regulator, adhesive, water, etc. to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 130°C for 1 hour and roasted at 400°C for 6 hours in an air atmosphere. Then, 60g of alumina was weighed out and uniformly mixed with an adhesive, acidity regulator, water, etc. to prepare a slurry, which was then applied to the roasted cordierite ceramic honeycomb carrier. The slurry was then dried at 90°C for 3 hours and roasted at 550°C for 1 hour in an air atmosphere to obtain a honeycomb-type precious metal catalyst Pt(1.6g / L) / Ce 0.20 Mn 0.25 La0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. A catalytic performance test was conducted on the above honeycomb-type precious metal catalyst, and the maximum NO conversion rate was 78.53%, the temperature corresponding to the maximum NO conversion rate was 249°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 69.83%.
[0104] (Example 52) A certain amount of Al2O3 was weighed and uniformly mixed with an acidity regulator, adhesive, water, etc. to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier. The honeycomb carrier was then dried at 140°C for 3 hours, and roasted at 600°C for 8 hours in an air atmosphere. A certain amount of Pt(1.0wt%) / Ce prepared in Example 44 was then added to the honeycomb carrier. 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.9 The catalyst was taken and mixed uniformly with adhesive, acidity regulator, water, etc. to prepare a slurry, which was then applied to the calcined cordierite ceramic honeycomb carrier, dried at 90°C for 3 hours, and calcined at 330°C for 6 hours to prepare the honeycomb-type precious metal catalyst Pt(1.0g / L) / Ce 0.20 Mn 0.25 La 0.05 Y 0.05 Fe 0.05 Zr 0.40 O 1.9 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 79.19%, the corresponding temperature for the maximum NO conversion rate was 239℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10%H2O / 100h was 70.37%.
[0105] (Example 53) A certain volume of platinum nitrate liquid salt with a Pt loading of 0.7 wt% was weighed out, uniformly mixed with alumina solid powder, dried at 70°C for 11 h, then heat-treated at 460°C for 5 h, and roasted at 550°C for 9 h in a H2 reducing atmosphere to obtain a catalyst Pt(0.7 wt%) / Al2O3. The above catalyst was uniformly mixed with an acidity regulator, adhesive, water, etc. to prepare a slurry, which was then applied to a cordierite ceramic honeycomb carrier. The coated honeycomb carrier was then dried at 130°C for 1 h, roasted at 400°C for 6 h in an air atmosphere, and then 60 g of Ce was added to the honeycomb carrier. 0.20 Mn 0.20 La 0.05 Y 0.05 Zinc 0.10 Zr 0.40 O 1.98 The mixture was weighed and uniformly mixed with adhesive, acidity regulator, water, etc. to prepare a slurry, which was then applied to the calcined cordierite ceramic honeycomb carrier, dried at 80°C for 8 hours, and calcined in an air atmosphere at 460°C for 6 hours to obtain a honeycomb-type precious metal catalyst Pt(1.0g / L) / Ce 0.20 Mn 0.20 La 0.05 Y 0.05 Zinc 0.10 Zr 0.40 O 1.98 -Al2O3 was obtained. The precious metal Pt was dispersed on the grain boundaries and surface of the alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 76.10%, the corresponding temperature for the maximum NO conversion rate was 266°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 67.83%.
[0106] (Example 54) A certain volume of platinum acetate liquid salt with a Pt loading of 1.0 g / L was weighed out and mixed uniformly with 50 g of alumina solid powder, acidity regulator, water, etc., and an adhesive was added to prepare a slurry, which was then applied to the first cordierite ceramic honeycomb carrier, dried at 100°C for 6 hours, heat-treated at 400°C for 6 hours, and roasted at 550°C for 7 hours in a H2 reducing atmosphere. Then, 50 g of Ce 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr0.58 The O2 was taken, mixed uniformly with acidity regulator, adhesive, water, etc. to prepare a slurry, which was then applied to the remaining second half of the cordierite ceramic honeycomb carrier, dried at 150°C for 2h, and roasted at 610°C for 5h to obtain the honeycomb-type precious metal catalyst Pt(1.0g / L) / Ce 0.14 Mn 0.16 La 0.03 Nd 0.04 Y 0.05 Zr 0.58 O2-Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the alumina. The catalytic performance test was carried out on the above honeycomb-type precious metal catalyst, and the maximum NO conversion rate was 79.13%, the corresponding temperature for the maximum NO conversion rate was 249℃, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650℃ / 10% H2O / 100h was 69.38%.
[0107] (Example 55) A certain volume of platinum nitrate liquid salt with a Pt loading of 0.7 g / L was weighed out and 0.20 Mn 0.15 Y 0.10 EU 0.05 Zr 0.50 O 1.99 The mixture is mixed with solid powder, acidity regulator, water, etc., and an adhesive is added to prepare a slurry. The slurry is applied to the first cordierite ceramic honeycomb carrier and dried at 100℃ for 6 hours. Then, an appropriate amount of alumina, acidity regulator, adhesive, water, etc. is taken and mixed uniformly to prepare a slurry. The slurry is applied to the remaining second cordierite ceramic honeycomb carrier, dried at 150℃ for 2 hours, and roasted at 610℃ for 5 hours to obtain the honeycomb-type precious metal catalyst Pt(0.7g / L) / Ce. 0.20 Mn 0.15 Y 0.10 EU 0.05 Zr 0.50 O 1.99 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide. The catalytic performance test was carried out on the above honeycomb-type precious metal catalyst, and the maximum NO conversion rate was 77.71%, the corresponding temperature for the maximum NO conversion rate was 266°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 64.93%.
[0108] (Example 56) A certain volume of platinum nitrate liquid salt is added to the substrate with a Pt loading of 1.5 g / L, and then uniformly mixed with a certain amount of alumina, acidity regulator, water, etc., and then an adhesive is added and mixed uniformly to prepare a coating slurry, which is then coated on the first cordierite ceramic honeycomb substrate, dried at 80°C for 9 hours, heat-treated at 380°C for 6 hours, and roasted at 610°C for 6 hours in a H2 reducing atmosphere, and then a certain amount of Ce is added. 0.40 Mn 0.10 La 0.05 Nd 0.05 W 0.20 Zr 0.20 O 1.98 The mixture was weighed and mixed with adhesive, acidity regulator, water, etc. to prepare a slurry, which was then applied to the remaining cordierite ceramic honeycomb carrier, dried at 150°C for 3 hours, and roasted at 460°C for 3 hours to prepare a honeycomb-type precious metal catalyst Pt(1.5g / L) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 W 0.20 Zr 0.20 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the alumina. The catalytic performance test was carried out on the above catalyst, and the maximum NO conversion rate was 81.79%, the corresponding temperature for the maximum NO conversion rate was 246°C, and the maximum NO conversion rate of the catalyst after hydrothermal aging at 650°C / 10% H2O / 100h was 71.51%.
[0109] (Example 57) A certain volume of platinum nitrate liquid salt with a Pt loading of 1.3 g / L was weighed out, and half of the platinum nitrate liquid salt was taken to remove Ce. 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98, acidity regulator, water, etc. uniformly mixed, then adhesive is added and mixed uniformly to prepare coating slurry, which is then coated on the first half of the cordierite ceramic honeycomb carrier, dried at 80°C for 9 hours, heat-treated at 380°C for 6 hours, and roasted at 610°C for 6 hours in a H2 reducing atmosphere; then the remaining half of the platinum nitrate liquid salt is taken and uniformly mixed with alumina, acidity regulator, water, etc., adhesive is added and mixed uniformly to prepare slurry, which is then coated on the remaining second half of the cordierite ceramic honeycomb carrier, dried at 150°C for 3 hours, heat-treated at 460°C for 6 hours, and roasted at 600°C for 5 hours in a H2 reducing atmosphere to prepare honeycomb-type precious metal catalyst Pt(1.3g / L) / Ce 0.40 Mn 0.10 La 0.05 Nd 0.05 Pr 0.20 Zr 0.20 O 1.98 -Al2O3 was obtained, and the precious metal Pt was dispersed on the grain boundaries and surface of the rare earth manganese zirconium composite oxide and alumina. The catalyst performance test was carried out on the above catalyst, and the maximum NO conversion rate was 80.16%, the temperature corresponding to the maximum NO conversion rate was 251°C, and the maximum catalyst NO conversion rate after hydrothermal aging at 650°C / 10%H2O / 100h was 70.09%. The above test process was to take an appropriate amount of catalyst with precious metals supported on the grain boundaries and surface and cut-out honeycomb-type precious metal catalyst samples and carry out catalytic performance tests respectively. The catalytic activity evaluation test was carried out by placing them in a microreactor, and the NO, NO2 and NO at the corresponding temperatures were measured by an infrared gas analyzer. x The content of is recorded, and the maximum conversion rate of NO of each catalyst fresh sample and the corresponding temperature are calculated, and the maximum conversion rate of NO after the sample is aged under hydrothermal conditions of 650℃ / 10%H2O / 100h. The catalyst test adopts a simulated automobile exhaust gas mixture, and the contents (volume occupancy ratio) of each component are 8% oxygen, 10% water, 500ppm carbon monoxide, 500ppm nitrogen monoxide, 200ppm C3H6, and 100ppm C3H8, and the equilibrium gas is nitrogen gas. The reaction temperature is set to increase from room temperature to 400℃ at a rate of 20℃ / min, and the reaction time is 20min.
[0110] As can be seen from the above experimental results, by using the catalyst with precious metals supported on the grain boundaries and surfaces and the honeycomb-type precious metal catalyst provided by the embodiment of the present invention, the NO conversion rates of the fresh and aged catalyst samples are significantly higher than those of the comparative catalyst samples, and the temperature corresponding to the maximum NO conversion rate of the fresh catalyst sample is also lower than that of the comparative catalyst sample. By diffusing the precious metals on the grain boundaries and surfaces, a multi-phase interface is formed, which reduces the lattice oxygen activation energy and increases the amount of active oxygen, while preventing the migration and growth of precious metal particles, so that the catalyst with precious metals supported on the grain boundaries and surfaces and the honeycomb-type precious metal catalyst provided by the embodiment of the present invention can significantly improve the low-temperature catalytic activity and high-temperature stability of NO oxidation.
[0111] In summary, the present invention relates to a catalyst with precious metal supported on grain boundaries and surfaces, and its manufacturing method and use, in which the precious metal G is uniformly dispersed on the grain boundaries and surfaces of alumina and / or rare earth manganese zirconium composite oxide to form a multi-phase interface, which obtains the following beneficial technical effects: 1. the multi-phase interface has greater steric hindrance and stronger anchoring effect, which inhibits the high-temperature migration, aggregation and growth of the precious metal, improves the high-temperature stability of the precious metal, and reduces the amount of precious metal used; 2. the multi-phase interface has a synergistic catalytic effect, which reduces the lattice oxygen activation energy and increases the amount of active oxygen, thereby improving the NO oxidation conversion rate and low-temperature catalytic activity.
[0112] It should be understood that the above specific embodiments of the present invention are merely used to exemplarily explain or interpret the principles of the present invention, and are not intended to limit the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention should be included within the protection scope of the present invention. Furthermore, the claims of the present invention are intended to include all changes and modifications that are included within the scope and boundaries of the claims, or are equivalent to the scope and boundaries.
Claims
1. A catalyst having a precious metal supported on grain boundaries and surfaces, the catalyst comprising a precious metal G, alumina and / or a rare earth manganese zirconium composite oxide, the precious metal G being dispersed on grain boundaries and surfaces of the alumina and / or rare earth manganese zirconium composite oxide, the rare earth manganese zirconium composite oxide having a general chemical formula of RE a Mn b Zr c M d O (2-δ) D β where: RE is a rare earth element, M is a cationic doping element, and D is an anionic doping element; 1. A catalyst having a precious metal supported on grain boundaries and a surface, characterized in that 0.1≦a≦0.5, 0.05≦b≦0.3, 0.2≦c≦0.8, 0≦d≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d=1.
2. A honeycomb-type precious metal catalyst, the catalyst comprising a honeycomb carrier, a precious metal G and an active coating, the active coating being alumina and / or a rare earth manganese zirconium composite oxide RE. a Mn b Zr c M d O (2-δ) D β said precious metal G being dispersed at the grain boundaries and surface of the active coating, wherein RE is a rare earth element, M is a cationic doping element, and D is an anionic doping element; 1. A honeycomb-type precious metal catalyst, characterized in that 0.1≦a≦0.5, 0.05≦b≦0.3, 0.2≦c≦0.8, 0≦d≦0.2, 0≦δ≦0.1, 0≦β≦0.1, and a+b+c+d=1.
3. The honeycomb catalyst according to claim 2, wherein the proportion of the rare earth manganese zirconium composite oxide in the total mass of the active coating is 0-100%, preferably 30-70%.
4. 4. The catalyst according to claim 1, wherein the noble metal G at the grain boundaries and on the surface is in the metallic state or in the metallic and oxidized states.
5. 5. The catalyst according to claim 1, wherein the precious metal G comprises one or a combination of one or more of Pt, Pd, Rh, Ir, Os, Ru, Au and Ag, preferably one or a combination of one or more of Pt, Pd, Rh and Ru, more preferably a combination of Pt and Pd.
6. 6. The catalyst according to any one of claims 1 to 5, characterized in that the rare earth elements RE comprise one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc, preferably one or a combination of one or more of La, Ce, Pr, Nd, Sm, Eu, Gd, Yb and Y, the doping elements M comprise one or a combination of one or more of transition metal elements, alkaline earth metal elements and Al, Si, Sn, and the doping elements D comprise one or a combination of one or more of anions N, P and F.
7. 7. The catalyst according to claim 6, wherein the transition metal element is one or a combination of one or more of Fe, Co, Ni, Cu, Zn, Ti, Hf, V, Cr, Nb, Mo and W, preferably one or a combination of one or more of Fe, Co, Ni, Cu and Hf, and the alkaline earth metal element is one or a combination of one or more of Mg, Ca, Sr and Ba, preferably one or a combination of one or more of Sr and Ba.
8. The catalyst having a precious metal supported on the grain boundaries and surface according to claim 1, characterized in that the amount of the precious metal G supported in the catalyst is 0.01% to 2% by mass, preferably 0.1% to 1% by mass.
9. 3. The honeycomb catalyst according to claim 2, wherein the amount of the precious metal G supported in the catalyst is 0.03 to 2.0 g / L, and preferably 0.15 to 1.5 g / L.
10. The catalyst according to any one of claims 1 to 9, characterized in that the rare earth manganese zirconium composite oxide in the catalyst comprises a core-shell structure, the core comprising rare earth and zirconium elements, and the shell comprising rare earth and manganese elements.
11. 10. The catalyst according to claim 1, wherein the rare earth manganese zirconium composite oxide in the catalyst contains a rare earth zirconium oxide having an element gradient distribution structure.
12. 3. The honeycomb type catalyst according to claim 2, wherein the material of the honeycomb carrier is a porous ceramic or a metal.
13. A step S1 of uniformly mixing a rare earth manganese zirconium composite oxide and / or alumina with a liquid salt of a precious metal G and drying the mixture; Step S2, which performs one or two heat treatments on the product obtained in step S1; and step S3 of roasting the product obtained in step S2 once or twice in air or a reducing atmosphere to obtain a catalyst having a precious metal supported on the grain boundaries and surfaces of the rare earth manganese zirconium composite oxide and / or alumina.
14. The honeycomb-type precious metal catalyst is coated with one or more coating materials in a hierarchical or compartmental manner, and the coating materials are selected from the group consisting of alumina, rare earth manganese zirconium composite oxide, alumina having a precious metal supported on its grain boundaries and surfaces, rare earth manganese zirconium composite oxide having a precious metal supported on its grain boundaries and surfaces, and a mixture of rare earth manganese zirconium composite oxide and alumina having a precious metal supported on its grain boundaries and surfaces. The manufacturing steps are: Step A1: uniformly mixing the one or more coating materials with an adhesive, an acidity adjuster and water in one or multiple steps to prepare a coating slurry; Step A2 of applying the coating slurry obtained in step A1 to a honeycomb carrier in one or multiple steps, or applying the coating slurry to the honeycomb carrier in a sectioned or layered manner, and then drying the coating slurry; A method for producing a honeycomb-type precious metal catalyst described in any one of claims 2 to 7 and 9 to 12, characterized in that it includes a step A3 of heat-treating and / or roasting the product obtained in step A2 in air or a reducing atmosphere to obtain a honeycomb-type precious metal catalyst.
15. The method for producing a honeycomb-type precious metal catalyst according to any one of claims 2 to 7 and 9 to 12, characterized in that a rare earth manganese zirconium composite oxide and / or alumina, a liquid salt of a precious metal G, an acidity regulator, an adhesive and water are uniformly mixed in one or multiple steps to prepare a coating slurry, the slurry is applied to a honeycomb carrier in one or multiple steps, or the honeycomb carrier is applied in sections or layers and dried, and the dried honeycomb carrier is heat-treated and / or roasted in a reducing atmosphere to obtain a honeycomb-type precious metal catalyst.
16. The method according to any one of claims 13 to 15, characterized in that the heat treatment temperature is 200-750 ° C, and the heat treatment time is 0.5-24 h, preferably, the heat treatment temperature is 400-700 ° C, and the heat treatment time is 1-12 h.
17. The method according to any one of claims 13 to 15, wherein the roasting temperature is 400-850°C and the time is 0.5-24h, preferably the roasting temperature is 450-750°C and the time is 1-12h.
18. 16. The method of claim 13 or 15, wherein the liquid salt of the precious metal G comprises one or a combination of one or more of the following molten salts or aqueous solutions of chlorides, nitrates, acetates and citrates.
19. The reducing atmosphere is CO and H 2 The method according to any one of claims 13 to 15, characterized in that it comprises one or more of the following:
20. Use of the catalyst according to any one of claims 1 to 12 in the fields of automobile exhaust gas purification, industrial organic exhaust gas treatment, natural gas catalytic combustion, petrochemistry, hydrogen energy, and batteries.
Citation Information
Patent Citations
Combustion catalyst for gas turbine
JP1984062344A
Dispersed noble metal-containing alumina particle, its preparation process and exhaust gas purification catalyst
JP2002066335A
Exhaust gas cleaning catalyst
JP2002079097A